Community psychiatric nursing in mental health, in Alava. «From hospital to... the community» - Fabiola Gasiain Sáenz; Ana I. Ramírez Gorostiza; Edurne Zurbano Sáenz (Universidad de Alicante, 1998)
The present study chronologically develops the evolution of mental health care in Alava together with the influence this mental health evolution has had in the Psychiatric Nursing profession. Since the opening of the Alava's Asilo Provincial (Home), in 1925, where different kind of patients - including mental health patients - received attention, to the present time, those professionals who have worked withing the Home premises, have discovered how care evolution towards these sort of patients has influenced not only the institutional procedures but how it has rendered easy as well the appearing of new roles for the Mental Health Nursing in the Community.